Access over 20 million homework & study documents
search

Img 20211202 wa0044

Content type

User Generated

Rating

Showing Page:
1/1

Sign up to view the full document!

lock_open Sign Up

Unformatted Attachment Preview

= (x+2)+ (-2) (By Associative) (+2) + (-2) = y + (2+(-2)) (uniqueness of zero) = y +0 = 9 x=y Hence the proof. et les con 고 Theonem :8.4 For each real number o, & -(-x) = x (ii) - (x+y) = (-x)+(-4) To pridef prove (1) Ty the negative 0-4 be denoted by z. ...
Purchase document to see full attachment
User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

Anonymous
Super useful! Studypool never disappoints.

Studypool
4.7
Trustpilot
4.5
Sitejabber
4.4